DEVELOPMENT OF TRACEABILITY SYSTEM FOR PRODUCT QUALITY ASSURANCE - Elena A. Yurova; Elena Yu. Parfenova; Maria I. Shramko; Anatoly V. Permyakov (Вестник Северо-Кавказского федерального университета, 2022)
The advanced technology, increasing competitiveness, dairy production of complex ingredient composition - all these determine the need for quality traceability systems to be introduced into the manufacturing process of enterprises adapted for production sites that have increased risk criteria. The dataset of a comprehensive study of raw milk on its physical, chemical and organoleptic features, as well as on the identification features and protein composition, allowed the development of quality traceability system adapted for the production of yoghurt and yoghurt products in view of the specific nature of the technology and the raw milk used.